Eclecticism In Counselling - Conklin, R. C.; Wiley, H. J. (Canadian Journal of Counselling and Psychotherapy, 2012)
A model was proposed for matching client problems with counselling approaches within the framework of an eclectic stance. Problems were grouped according to client's needs which related to Maslow's hierarchy.Counselling approaches were similarly grouped and a schematic relationship presented. A thesis was advanced that certain client problems arebest handled using differential counselling techniques.